The cost of copy number in a selfish genetic element: the 2-μm plasmid of Saccharomyces cerevisiae. - Harrison, E; Koufopanou, V; Burt, A; Maclean, C (2012)
Many autonomously replicating genetic elements exist as multiple copies within the cell. The copy number of these elements is often assumed to have important fitness consequences for both element and host, yet the forces shaping its evolution are not well understood. The 2 μm is a multicopy plasmid of Saccharomyces yeasts, encoding just four genes that are solely involved in plasmid replication. One simple model for the fitness relationship between yeasts and 2 μm is that plasmid copy number evolves as a trade-off between selection for increased vertical transmission, favouring high copy number, and selection for decreased virulence, favouring low copy number. To test this model, we experimentally manipulated the copy number of the plasmid and directly measured the fitness cost, in terms of growth rate reduction, associated with high plasmid copy number. We find that the fitness burden imposed by the 2 μm increases with plasmid copy number, such that each copy imposes a fitness burden of 0.17% (± 0.008%), greatly exceeding the cost expected for it to be stably maintained in yeast populations. Our results demonstrate the crucial importance of copy number in the evolution of yeast per 2 μm associations and pave the way for future studies examining how selection can shape the cost of multicopy elements.